Disabled people's experiences accessing healthcare services during the COVID-19 pandemic: a scoping review - Karen McBride-Henry; Solmaz Nazari Orakani; Gretchen Good; Michael Roguski; Tara N. Officer (BMC, 2023)
Abstract Background Disruptions to healthcare services during the COVID-19 pandemic are well-recognised problems. However, a dearth of research exists on disabled people's experiences with accessing these services. A scoping review was undertaken to identify and explore research on the experience of disabled people in accessing healthcare services between 2020 and 6 February 2023. Methods PubMed, Web of Science, CINAHL, and OVID were employed to search for research that included the voice of disabled people, or their parents or caregivers. Over two distinct phases, a total of 2,201 articles were reviewed according to article titles, keywords, and abstracts. Eighty-one studies were identified that met the inclusion criteria; these were reviewed in full. Results Eighteen studies specifically described the experiences of accessing healthcare or disability services, and sixty-three raised healthcare challenges as a secondary consideration. Many disabled people struggled to access healthcare services and felt they were invisible; as a result, individuals' mental health was negatively affected. Disabled people with compounding vulnerabilities were at the most risk of experiencing a lack of healthcare access. Conclusions There is an urgent need for research and policy that is responsive to disabled people's access to healthcare during the pandemic; currently many health policies are 'disability-blind' and exclude these members of the global community. Furthermore, to assist in creating disability-responsive research, funding needs to prioritise researchers within the disabled community.